Correlation Between Live Weight and Carcass Weight and Giblet Weight In Broiler Chickens Given White Turmeric Extract - Horhoruw, Wiesje; Ismael Kewilaa, Arnold (Advances In Social Humanities Research, 2024)
The objective of this research is to determine the correlation between live weight, carcass weight, and giblet weight in broiler chickens given 4% white turmeric extract. This study was conducted from July to September 2024 at the Poultry Unit of the Animal Husbandry Department, Faculty of Agriculture, Pattimura University Ambon. The materials used in this research were 60 Cobb strain broiler chickens. The feed provided consisted of BR1 and BR2 produced by PT. Malindo Feedmilk, vita stress, and Gumboro vaccine. The white turmeric extract administered was 40 ml from a total of 1000 ml of drinking water (4% white turmeric extract). The data analysis technique used in this study was simple linear regression statistical testing to examine the effect of the independent variable (live weight) on the dependent variable (carcass weight) of broiler chicken at a significance level (?) = 0.05. Data processing was performed using the SPSS computer program. The results showed that live weight had a very strong (0.992) and positive correlation with carcass weight in broiler chickens given 4% white turmeric extract, while live weight and giblet weight had a strong (0.711) and positive correlation